Between Liberal Aspirations and Market Forces: Obamacare's Precarious Balancing Act. Issue 4 (2014) - Oberlander, Jonathan
Abstract : The American health care system long has been distinctive in its embrace of market forces. For-profit private insurers play a major role in providing coverage, though they operate alongside public insurance programs that cover over one-third of the population. Historically, federal and state governments' regulation of insurance markets was limited, leaving insurers to set premiums and coverage rules largely as they saw fit. Government's role in controlling health care spending has been even more circumscribed. Purchasing power is fragmented, with each insurer negotiating its own rates with physicians and hospitals. A formidable medical-industrial complex of for-profit providers, from hospitals to home-health care agencies, dialysis facilities, pharmaceutical companies and much more, has arisen to sell services.